Insights into the composition and properties of fly ash emissions from a municipal solid waste power plant - Tra Mai Ngo; Van Hung Hoang; Huu Tap Van; Hang Nguyen Thi Thuy; Hong Khuat Thi; Nghiem Thi Ha Lien; Nguyen Trong Nghia; Phan Thi Thanh Hang; Vu Duc Toan; Trinh Thi Tham; Nguyen Thi Hoa (Environmental Research Communications, 2024)
This study examines the fly ash from Soc Son municipal waste power plant (SMPP) and suggests ways to repurpose it to reduce its environmental impact. Fly ash from the Soc Son waste power plant has a gray color, spherical particles with a 5–103 μ m diameter, and a high carbon and heavy metal content. Bermorite crystals can absorb and release heavy metals, making monitoring secondary pollutants during incineration crucial. The EDX analysis of fly ash from the Soc Son waste power plant revealed that it was predominantly contaminated with metal elements, with the highest percentage of calcium. The EDX was able to detect heavy metals in incinerator fly ash. The concentration of Zn in the fly ash exceeded QCVN 07:2009/BTNMT standards, indicating the high amounts of some elements that may be hazardous to the environment and human health. Using the SEM/EDX and XRF, the fly ash from the Soc Son landfill power plant was analyzed and discovered that it exceeds permissible limits for dangerous heavy elements. The most common inorganic elements are Ca, followed by Zn, Pb, Cd, and Ag. Fly ash is classed as hazardous waste due to its high concentration of heavy metals, which results from the combustion of municipal solid waste that has not been separated. Vietnam fights municipal solid waste incinerator fly ash production. Some nations stabilize fly ash to remove harmful components and use it in buildings. Stabilized fly ash makes unfired construction bricks and cement manufacturing components and combining fly ash with inorganic trash protects the environment.